Putting xanthine oxidoreductase and aldehyde oxidase on the NO metabolism map: Nitrite reduction by molybdoenzymes - Maia, Luisa B. (2018)
We acknowledge Fundacao para a Ciencia e Tecnologia (FCT/MCTES) for the financial support granted to the Associate Laboratory for Green Chemistry - LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER - 007265). LBM also thanks to FCT/MCTES for the fellowship grant (SFRH/BPD/111404/2015, which is financed by national funds and co-financed by FSE).